Improving Individual Innovative Behavior and Post-COVID-19 Student’ Learning Outcomes Through Project-Based Blended Learning - Joko Joko; Ismet Basuki; Tri Rijanto; Muhamad Syariffuddien Zuhrie; Fendi Achmad (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to improve individual innovative behavior and learning outcomes and determine differences in individual innovative behavior and student learning outcomes after being taught with Project_Based Blended Learning synchronous and asynchronous online models followed by face-to-face offline models in the post-COVID-19 era. Method: The research used a quasi-experiment; the control class samples were 33, and the experimental class was 33 students. Data were collected using questionnaires, test instruments, and observation sheets, and the collected data were analyzed using descriptive statistics, gain tests, and t-tests. Result: The increase in individual innovative behavior and learning outcomes before and after teaching in the control class in the moderately effective category is lower and significantly different compared to the experimental class in the practical category. The final score of individual innovative behavior and learning outcomes of the control class is lower and significantly different than that of the experimental class. Novelty: Blended Learning in this research is integrated with Project-Based Learning with synchronous and asynchronous online models to produce project products assigned to be used in practical courses.